If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3x + 20) = 14(2x + -3) Reorder the terms: 5(20 + 3x) = 14(2x + -3) (20 * 5 + 3x * 5) = 14(2x + -3) (100 + 15x) = 14(2x + -3) Reorder the terms: 100 + 15x = 14(-3 + 2x) 100 + 15x = (-3 * 14 + 2x * 14) 100 + 15x = (-42 + 28x) Solving 100 + 15x = -42 + 28x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-28x' to each side of the equation. 100 + 15x + -28x = -42 + 28x + -28x Combine like terms: 15x + -28x = -13x 100 + -13x = -42 + 28x + -28x Combine like terms: 28x + -28x = 0 100 + -13x = -42 + 0 100 + -13x = -42 Add '-100' to each side of the equation. 100 + -100 + -13x = -42 + -100 Combine like terms: 100 + -100 = 0 0 + -13x = -42 + -100 -13x = -42 + -100 Combine like terms: -42 + -100 = -142 -13x = -142 Divide each side by '-13'. x = 10.92307692 Simplifying x = 10.92307692
| 3q+7=6q-1 | | b^2=-4b-3 | | 5=n-6n | | =2.5 | | 8p+13=61 | | 2x^2+24x=176 | | 3x+9=8(x-16) | | 2(5+b)=3(b-2) | | (y-0)=-3(x-3) | | 8x=5x+7whatisx | | 0=8x^3-11x^2+14x-9 | | 8x+20=2x-10 | | 100-7r=45 | | 4+2(4x-6)=5-5(2x+1) | | 8x^4y^2+40x^2y^2-72x^2y= | | 3x=8x-119 | | 100-7t=44 | | 0.50+(12-x)=0.10(-57) | | x^3-12x^2-151x+1122=0 | | 22-7k=-2(6k-6) | | 4m^2-36m+81= | | -6=7x+-2 | | 6(3m+5)=-28 | | 33=8+5t | | -92=7(a-8)+6 | | 8y-10=0 | | 2.7xa=8.37 | | -3(x)=-3x*3+7 | | 2x-7=x+9 | | Ln(7-3x)=-4 | | (5m)+(2m)-5= | | y=3.25+2.5 |